Preparation method of microporous damp-heat migration-resistant microfiber synthetic leather based on waterborne polyurethane and application of microporous damp-heat migration-resistant microfiber synthetic leather in automotive trim

Through nano-silica doping technology and alkaline treatment, a three-dimensional crosslinking network and hollow micropores were constructed, which solved the problem of uneven distribution of polyurethane in the drying process of water-based polyurethane synthetic leather, and improved the feel, softness and Breathability, suitable for high demanding automotive interiors.

CN119392494APending Publication Date: 2025-02-07SHAOXING UNIVERSITY
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411523540.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The polyurethane synthetic leather of water-based polyurethane is unevenly distributed during the drying process, resulting in hard feel, uneven pore size and distribution of the product, making it difficult to apply to the high-demand automotive interior fields.

Method used

Using nano-silica doping technology to build a three-dimensional cross-linking network between microfibers and aqueous polyurethanes, the open fibers of microfibers and the hydrolysis and removal of nano-silicas are achieved through alkaline treatment, thereby building a hollow micrometer with controllable size Pores to improve the moisture and heat migration resistance of synthetic leather.

Benefits of technology

It improves the feel, softness and breathability of the water-based ultra-fiber synthetic leather, and simultaneously solves the two major problems of cell uniformity and moisture and heat resistance, and is suitable for high-demand fields such as automotive interiors.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119392494A_ABST
    Figure CN119392494A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of synthetic leather fabrics, in particular to a preparation method of microporous damp-heat migration-resistant microfiber synthetic leather based on waterborne polyurethane and application of the microporous damp-heat migration-resistant microfiber synthetic leather in automotive interiors. The method comprises the following steps: step 1, preparing a nano SiO2 doped WPU solution; step 2, immersing the superfine fiber leather base cloth into the nano SiO2 doped WPU solution, dipping twice and rolling twice, and drying to obtain superfine fiber synthetic leather grey cloth; and carrying out alkali decrement hydrolysis treatment on the microfiber synthetic leather gray fabric to obtain the waterborne polyurethane-based microporous moisture-heat migration-resistant microfiber synthetic leather. The nano SiO2 doping technology synchronously solves the two problems of bubble uniformity and damp-heat migration resistance of the waterborne polyurethane synthetic leather, the hand feeling, the softness and the air permeability of the microfiber synthetic leather product are improved, and the prepared microporous damp-heat migration-resistant microfiber synthetic leather based on the waterborne polyurethane can be applied to automotive interiors.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of fabrics, and in particular to a method for preparing a microporous moisture-heat migration-resistant ultra-fiber synthetic leather based on waterborne polyurethane and an application thereof in automobile interior decoration. Background Art

[0002] Waterborne polyurethane is a polymer emulsion formed by dispersing polyurethane in water instead of the organic solvent in traditional solvent-based polyurethane. Due to the advantages of no organic solvent, low VOC release, little harm to production personnel, and green environmental protection, waterborne polyurethane is increasingly widely used in the field of synthetic leather. However, compared with solvent-based polyurethane, there are still many shortcomings in the microfiber synthetic leather made of waterborne polyurethane. First of all, because waterborne polyurethane contains more hydrophilic groups, when the waterborne microfiber leather is dried, the polyurethane will move to both sides of the synthetic leather with the evaporation of water, and finally concentrate on the surface of the synthetic leather, which causes the phenomenon of uneven distribution of polyurethane in the synthetic leather. In addition, because the waterborne polyurethane molecules exist in the state of emulsion particles, the large particle size leads to relatively poor stability, film-forming properties, wettability and bonding properties of the emulsion to the base fabric, so that the waterborne polyurethane impregnated microfiber leather is prone to problems such as tensile cracking, hard feel, uneven pore size and distribution. Therefore, although water-based synthetic leather has advantages such as being environmentally friendly and non-toxic, it has always been limited to use in low- and medium-end fields such as shoes and hats, and it is difficult to expand to the field of automotive interiors, which have high requirements for various physical properties. Summary of the invention

[0003] In view of the deficiencies of the prior art, the present invention provides a method for preparing microporous moisture-heat migration-resistant ultra-fine synthetic leather based on waterborne polyurethane and its application in automobile interior decoration, and adopts nano-silicon dioxide doping technology to construct a three-dimensional cross-linked network between ultra-fine fibers and waterborne polyurethane, so as to improve the problem that the resin moves to both sides with the evaporation of water during the dry molding process, resulting in the lack of resin matrix in the core of the prepared synthetic leather. After the material is molded, an alkaline method is used to simultaneously realize the opening of the ultra-fine fibers and the hydrolysis and removal of nano-silicon dioxide, thereby constructing hollow micropores of controllable size inside the ultra-fine fiber / waterborne polyurethane synthetic leather, and improving the feel, softness and air permeability of the waterborne ultra-fine synthetic leather product. The two major problems of pore uniformity and moisture-heat migration resistance of waterborne polyurethane synthetic leather in the prior art are solved simultaneously, and the application disadvantages of the dry molding process are avoided.

[0004] In order to achieve the above object, the technical solution adopted by the present invention is as follows:

[0005] A method for preparing microporous moisture-heat migration-resistant ultra-fiber synthetic leather based on waterborne polyurethane comprises the following steps:

[0006] Step 1: Preparation of nano-SiO2 doped WPU solution

[0007] The nano-SiO2 system and the WPU (waterborne polyurethane) solution are mixed in a mass ratio of 1:(1-3), and after stirring, a nano-SiO2-doped WPU solution is obtained;

[0008] Step 2: Preparation of microporous moisture-heat migration-resistant microfiber synthetic leather based on waterborne polyurethane

[0009] The ultrafine fiber leather base cloth is immersed in the nano-SiO2 doped WPU solution, double-immersed and double-rolled, and dried to obtain the ultrafine fiber synthetic leather grey cloth;

[0010] The microfiber synthetic leather grey cloth is immersed in an alkali solution for alkali reduction and hydrolysis treatment to obtain a microporous moisture-heat migration-resistant microfiber synthetic leather based on waterborne polyurethane.

[0011] Preferably, in step 1, the nano-SiO2 system includes any one of nano-SiO2 sol and nano-SiO2 dispersion.

[0012] Preferably, the nano-SiO2 sol is prepared by the following steps:

[0013] Sodium dodecylbenzenesulfonate and concentrated hydrochloric acid are added to deionized water and mixed. After the sodium dodecylbenzenesulfonate is completely dissolved, methyltrimethoxysilane is added dropwise. After the addition is completed, the reaction is stirred. After the reaction is completed, the temperature is increased to continue the reaction. After the reaction is completed, the reaction is cooled and the pH value is adjusted to 6-7 to obtain a nano-SiO2 sol.

[0014] Preferably, the stirring reaction condition is to maintain a stirring speed of 300 r / min, first react at a temperature of 20-40° C. for 0.5-1.5 h, then heat to 50-70° C., and continue to react for 0.5-2.5 h.

[0015] Preferably, when preparing nano-SiO2 sol, the amount of methyltrimethoxysilane is 20-150 g / L, the amount of sodium dodecylbenzenesulfonate is 0.2-1.2 g / L, and the amount of concentrated hydrochloric acid is 0.5-5 g / L;

[0016] The concentrated hydrochloric acid is a 37 wt % hydrochloric acid aqueous solution.

[0017] Preferably, the nano-SiO2 dispersion is prepared by uniformly dispersing nano-SiO2 particles in deionized water.

[0018] Preferably, the nano-SiO2 particles used in the preparation of the nano-SiO2 dispersion have a particle size of 30nm-3μm and a content of 20-240g / L, and the dispersion methods include stirring dispersion, ultrasonic dispersion, and high-performance disperser dispersion.

[0019] Preferably, in the step 2, the liquid carrying rate after the double dipping and double rolling is 100%, and the drying conditions are first drying at 80-100° C. for 15-30 min, and then drying at 120-150° C. for 10-30 min.

[0020] Preferably, in the step 2, the alkali reduction hydrolysis treatment comprises immersing the microfiber synthetic leather grey cloth in an alkali solution for hydrolysis treatment, the bath ratio of the grey cloth to the alkali solution is 1:10, and the alkali solution comprises a 4-30 g / L sodium hydroxide aqueous solution.

[0021] Preferably, the alkali reduction hydrolysis process comprises: heating to 95-125° C. at a rate of 2° C. / min, and maintaining the temperature for hydrolysis for 30-90 min.

[0022] Preferably, the ultrafine fiber leather base fabric can be dyed by adding active dyes to the nano-SiO2-doped WPU solution.

[0023] A method for preparing microporous moisture-heat migration resistant microfiber synthetic leather based on waterborne polyurethane as described above is used in automobile interior decoration.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] Nano-SiO2 doping technology simultaneously solves the two major problems of pore uniformity and resistance to moisture and heat migration of water-based polyurethane synthetic leather, avoids the application disadvantages of dry molding process (which is simpler, more efficient and does not require a coagulation bath than wet molding process), and improves the feel, softness and breathability of microfiber synthetic leather products. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 The comparison photos of the nano-SiO2 dispersion sample after alkaline treatment (left) and without alkaline treatment (right) in Example 1 of the present invention;

[0027] Figure 2 The surface morphology of the nano-SiO2-doped WPU film prepared in Example 16 of the present invention observed using a SU3800 scanning electron microscope;

[0028] Figure 3 The surface morphology of the nano-SiO2-doped WPU film prepared in Example 17 of the present invention observed using a SU3800 scanning electron microscope;

[0029] Figure 4 The surface morphology of the nano-SiO2-doped WPU film prepared in Example 18 of the present invention observed using a SU3800 scanning electron microscope;

[0030] Figure 5The surface morphology of the nano-SiO2-doped WPU film prepared in Example 19 of the present invention observed using a SU3800 scanning electron microscope;

[0031] Figure 6 The cross-sectional morphology of the waterborne polyurethane-based ultra-fine synthetic leather prepared in Example 24 of the present invention observed using a SU3800 scanning electron microscope;

[0032] Figure 7 The cross-sectional morphology of the microporous moisture-heat migration-resistant ultra-fiber synthetic leather based on waterborne polyurethane prepared in Example 20 of the present invention observed using a SU3800 scanning electron microscope;

[0033] Figure 8 The cross-sectional morphology of the microporous moisture-heat migration-resistant ultra-fiber synthetic leather based on waterborne polyurethane prepared in Example 21 of the present invention observed using a SU3800 scanning electron microscope;

[0034] Fig. 9 The cross-sectional morphology of the microporous moisture-heat migration-resistant ultra-fiber synthetic leather based on waterborne polyurethane prepared in Example 22 of the present invention observed using a SU3800 scanning electron microscope;

[0035] Fig.10 The cross-sectional morphology of the microporous moisture-heat migration-resistant ultra-fiber synthetic leather based on waterborne polyurethane prepared in Example 23 of the present invention observed using a SU3800 scanning electron microscope;

[0036] Fig.11 The graph is a result of dyeing test on the waterborne polyurethane-based microfiber synthetic leather prepared in Examples 20-24. DETAILED DESCRIPTION

[0037] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0038] Example 1

[0039] This embodiment discloses a method for dispersing and alkaline treating nano-SiO2 particles, comprising the following steps:

[0040] The nano-SiO2 particles were mixed with deionized water and magnetically stirred at room temperature for 12 hours to obtain a 20 g / L nano-SiO2 dispersion. The nano-SiO2 dispersion was divided into two equal parts, one part was added with 25 g / L sodium hydroxide, and the other part was not added. The mixture was treated in a water bath at 98°C for 1 hour, and the phenomenon was observed. The average particle size and distribution of the nano-SiO2 particles in the two nano-SiO2 dispersions were measured. The results are shown in Table 1:

[0041] Table 1 Particle size of nano-SiO2 dispersion before and after treatment under alkaline conditions

[0042]

[0043] The particle size of 20g / L nano-SiO2 dispersion after stirring for 12h at room temperature is 314.5nm. It can be seen from Table 1 that the particle size of nano-SiO2 particles in the nano-SiO2 dispersion treated with alkaline is much smaller than that without alkaline treatment, and the PDI (polydispersity index) is small, and the solution system is more stable. The particle size of nano-SiO2 particles in the nano-SiO2 dispersion decreases after alkaline treatment, indicating that the nano-SiO2 particles are hydrolyzed under alkaline conditions. The particle size of the control sample without alkaline treatment increases, which may be due to the agglomeration of nano-SiO2 particles during high-temperature treatment.

[0044] Depend on Figure 1 It can be seen that the nano-SiO2 dispersion treated under alkaline conditions is clear and transparent, while the nano-SiO2 dispersion without alkali treatment is turbid, indicating that under alkaline conditions, the nano-SiO2 particles will be hydrolyzed and the solution will become transparent.

[0045] Example 2

[0046] This embodiment discloses a method for preparing a nano-SiO2 sol, comprising the following steps:

[0047] Sodium dodecylbenzene sulfonate and 37wt% hydrochloric acid aqueous solution are added to deionized water and mixed. After the sodium dodecylbenzene sulfonate is completely dissolved, methyltrimethoxysilane is added dropwise. After the addition is completed, the stirring speed is maintained at 300r / min, and the reaction is first carried out at 30°C for 1h, and then the temperature is raised to 60°C, and the reaction is continued at 60°C for 2h, and then cooled to room temperature. The pH value is adjusted to 7 with 2mol / L sodium hydroxide aqueous solution to obtain nano-SiO2 sol;

[0048] Wherein, the dosage of methyltrimethoxysilane is 60 g / L, the dosage of sodium dodecylbenzenesulfonate is 1.2 g / L, and the dosage of 37 wt % hydrochloric acid aqueous solution is 5 g / L.

[0049] Example 3

[0050] This embodiment discloses a method for preparing a nano-SiO2 sol, comprising the following steps:

[0051] Sodium dodecylbenzene sulfonate and 37wt% hydrochloric acid aqueous solution are added to deionized water and mixed. After the sodium dodecylbenzene sulfonate is completely dissolved, methyltrimethoxysilane is added dropwise. After the addition is completed, the stirring speed is maintained at 300r / min, and the reaction is first carried out at 30°C for 1h, and then the temperature is raised to 60°C, and the reaction is continued at 60°C for 2h, and then cooled to room temperature. The pH value is adjusted to 7 with 2mol / L sodium hydroxide aqueous solution to obtain nano-SiO2 sol;

[0052] Wherein, the dosage of methyltrimethoxysilane is 120 g / L, the dosage of sodium dodecylbenzenesulfonate is 1.2 g / L, and the dosage of 37 wt % hydrochloric acid aqueous solution is 5 g / L.

[0053] The particle size distribution of the nano-SiO2 sol obtained in Example 2 and Example 3 was measured, and the measurement results are shown in Table 2:

[0054] Table 2 Particle size of nano-SiO2 sol prepared under different methyltrimethoxysilane dosage conditions

[0055]

[0056] It can be seen from Table 2 that with the increase of methyltrimethoxysilane concentration, the sol particle size decreases instead. It may be that when the amount of methyltrimethoxysilane is too much, there are too many silanols in the system, which will affect the polymerization due to too much steric hindrance, making it difficult for the particles to grow, thereby resulting in a decrease in particle size.

[0057] Example 4

[0058] This embodiment discloses a method for preparing a nano-SiO2 dispersion, comprising the following steps:

[0059] The nano-SiO2 particles were mixed with deionized water, and the mixture was stirred and dispersed at room temperature for 12 hours using a magnetic stirrer at a stirring speed of 300 r / min to obtain a nano-SiO2 dispersion.

[0060] The content of nano-SiO2 in the nano-SiO2 dispersion is 120g / L.

[0061] Example 5

[0062] This embodiment discloses a method for preparing a nano-SiO2 dispersion, comprising the following steps:

[0063] The nano-SiO2 particles were mixed with deionized water, and the mixture was stirred and dispersed at room temperature for 12 hours with a magnetic stirrer at a stirring speed of 300 r / min to obtain a nano-SiO2 dispersion.

[0064] The content of nano-SiO2 in the nano-SiO2 dispersion is 240g / L.

[0065] Example 6

[0066] This embodiment discloses a method for preparing a nano-SiO2 dispersion, comprising the following steps:

[0067] The nano-SiO2 particles were mixed with deionized water and ultrasonically dispersed for 15 minutes to obtain a nano-SiO2 dispersion;

[0068] The content of nano-SiO2 in the nano-SiO2 dispersion is 120g / L.

[0069] Example 7

[0070] This embodiment discloses a method for preparing a nano-SiO2 dispersion, comprising the following steps:

[0071] The nano-SiO2 particles were mixed with deionized water and ultrasonically dispersed for 30 minutes to obtain a nano-SiO2 dispersion;

[0072] The content of nano-SiO2 in the nano-SiO2 dispersion is 120g / L.

[0073] Example 8

[0074] This embodiment discloses a method for preparing a nano-SiO2 dispersion, comprising the following steps:

[0075] The nano-SiO2 particles were mixed with deionized water and ultrasonically dispersed for 45 minutes to obtain a nano-SiO2 dispersion;

[0076] The content of nano-SiO2 in the nano-SiO2 dispersion is 120g / L.

[0077] Example 9

[0078] This embodiment discloses a method for preparing a nano-SiO2 dispersion, comprising the following steps:

[0079] The nano-SiO2 particles were mixed with deionized water and ultrasonically dispersed for 60 minutes to obtain a nano-SiO2 dispersion;

[0080] The content of nano-SiO2 in the nano-SiO2 dispersion is 120g / L.

[0081] Example 10

[0082] This embodiment discloses a method for preparing a nano-SiO2 dispersion, comprising the following steps:

[0083] The nano-SiO2 particles were mixed with deionized water and ultrasonically dispersed for 15 minutes to obtain a nano-SiO2 dispersion;

[0084] The content of nano-SiO2 in the nano-SiO2 dispersion is 240g / L.

[0085] Embodiment 11

[0086] This embodiment discloses a method for preparing a nano-SiO2 dispersion, comprising the following steps:

[0087] The nano-SiO2 particles were mixed with deionized water and ultrasonically dispersed for 30 minutes to obtain a nano-SiO2 dispersion;

[0088] The content of nano-SiO2 in the nano-SiO2 dispersion is 240g / L.

[0089] Example 12

[0090] This embodiment discloses a method for preparing a nano-SiO2 dispersion, comprising the following steps:

[0091] The nano-SiO2 particles were mixed with deionized water and ultrasonically dispersed for 45 minutes to obtain a nano-SiO2 dispersion;

[0092] The content of nano-SiO2 in the nano-SiO2 dispersion is 240g / L.

[0093] Example 13

[0094] This embodiment discloses a method for preparing a nano-SiO2 dispersion, comprising the following steps:

[0095] The nano-SiO2 particles were mixed with deionized water and ultrasonically dispersed for 60 minutes to obtain a nano-SiO2 dispersion;

[0096] The content of nano-SiO2 in the nano-SiO2 dispersion is 240g / L.

[0097] Embodiment 14

[0098] This embodiment discloses a method for preparing a nano-SiO2 dispersion, comprising the following steps:

[0099] The nano-SiO2 particles were mixed with deionized water and dispersed for 10 minutes using a high-performance disperser to obtain a nano-SiO2 dispersion;

[0100] The content of nano-SiO2 in the nano-SiO2 dispersion is 120g / L.

[0101] Embodiment 15

[0102] This embodiment discloses a method for preparing a nano-SiO2 dispersion, comprising the following steps:

[0103] The nano-SiO2 particles were mixed with deionized water and dispersed for 10 minutes using a high-performance disperser to obtain a nano-SiO2 dispersion;

[0104] The content of nano-SiO2 in the nano-SiO2 dispersion is 240g / L.

[0105] The particle size distribution of the nano-SiO2 dispersion obtained in Example 4-15 was measured, and the results are shown in Table 3:

[0106] Table 3 Particle size of nano-SiO2 dispersions with different concentrations treated by different dispersion methods

[0107]

[0108] As shown in Table 3, the particle size of 120g / L nano-SiO2 dispersion is larger than that of 240g / L nano-SiO2 dispersion, but the PDI of 120g / L nano-SiO2 dispersion is smaller, and the distribution is more concentrated than that of 240g / L nano-SiO2 dispersion, and the solution is relatively stable; the average particle size of the nano-SiO2 dispersion decreases with the increase of ultrasonic treatment time. Comparative Example 4, in Examples 6-9, the particle size of the 120g / L nano-SiO2 dispersion obtained by ultrasonic dispersion using ultrasound decreases, and the PDI increases, indicating that although the particle size of the nano-SiO2 dispersion decreases during the ultrasonic process, the solution state becomes unstable; Comparative Example 5, in Examples 10-13, the particle size of the 240g / L nano-SiO2 dispersion obtained by ultrasonic dispersion using ultrasound is not much different, and the PDI is also similar; when treated with a high-performance disperser, the particle size of the 120g / L nano-SiO2 dispersion is smaller than that of the 240g / L nano-SiO2 dispersion. L nano-SiO2 dispersion has a large particle size. In Example 4 and Example 14, the particle size of the 120g / L nano-SiO2 dispersion after being treated with a high-performance disperser is smaller than that treated with magnetic stirring, but the PDI becomes larger, indicating that although the particle size of the nano-SiO2 dispersion becomes smaller during the treatment with the high-performance disperser, the solution state becomes unstable; in Example 5 and Example 15, the particle size of the 240g / L nano-SiO2 dispersion after being treated with a high-performance disperser is not much different from that treated with magnetic stirring, and the PDI is also similar.

[0109] Example 16

[0110] This embodiment discloses a method for preparing a nano-SiO2 doped WPU film, comprising the following steps:

[0111] (1) Mixing the nano-SiO2 sol prepared in Example 2 with WPU, with the mass ratio of nano-SiO2 sol to WPU being 1:3, and stirring for 30 min to obtain a nano-SiO2-doped WPU solution;

[0112] (2) Pour the nano-SiO2-doped WPU solution into a glass dish with a film-laying height of 5 mm. Bake the glass dish at 85°C for 30 min and then at 130°C for 2 h to obtain a dried film.

[0113] (3) immersing the dried film in a 23 g / L sodium hydroxide aqueous solution for alkali reduction hydrolysis treatment at a bath ratio of 1:10 to obtain a nano-SiO2-doped WPU film;

[0114] The alkali reduction hydrolysis process is as follows: heating to 100°C at a rate of 2°C / min, and hydrolyzing at 100°C for 60 minutes.

[0115] Embodiment 17

[0116] This embodiment discloses a method for preparing a nano-SiO2 doped WPU film, comprising the following steps:

[0117] (1) Mixing the nano-SiO2 sol prepared in Example 3 with WPU, with the mass ratio of nano-SiO2 sol to WPU being 1:3, and stirring for 30 min to obtain a nano-SiO2-doped WPU solution;

[0118] (2) Pour the nano-SiO2-doped WPU solution into a glass dish with a film-laying height of 5 mm. Bake the glass dish at 85°C for 30 min and then at 130°C for 2 h to obtain a dried film.

[0119] (3) immersing the dried film in a 23 g / L sodium hydroxide aqueous solution for alkali reduction hydrolysis treatment at a bath ratio of 1:10 to obtain a nano-SiO2-doped WPU film;

[0120] The alkali reduction hydrolysis process is as follows: heating to 100°C at a rate of 2°C / min, and hydrolyzing at 100°C for 60 minutes.

[0121] Embodiment 18

[0122] This embodiment discloses a method for preparing a nano-SiO2 doped WPU film, comprising the following steps:

[0123] (1) Mixing the nano-SiO2 dispersion prepared in Example 4 with WPU, with the mass ratio of the nano-SiO2 dispersion to WPU being 1:3, and stirring for 30 min to obtain a nano-SiO2-doped WPU solution;

[0124] (2) Pour the nano-SiO2-doped WPU solution into a glass dish with a film-laying height of 5 mm. Bake the glass dish at 85°C for 30 min and then at 130°C for 2 h to obtain a dried film.

[0125] (3) immersing the dried film in a 23 g / L sodium hydroxide aqueous solution for alkali reduction hydrolysis treatment at a bath ratio of 1:10 to obtain a nano-SiO2-doped WPU film;

[0126] The alkali reduction hydrolysis process is as follows: heating to 100°C at a rate of 2°C / min, and hydrolyzing at 100°C for 60 minutes.

[0127] Embodiment 19

[0128] This embodiment discloses a method for preparing a nano-SiO2 doped WPU film, comprising the following steps:

[0129] (1) Mixing the nano-SiO2 dispersion prepared in Example 5 with WPU, with the mass ratio of the nano-SiO2 dispersion to WPU being 1:3, and stirring for 30 min to obtain a nano-SiO2-doped WPU solution;

[0130] (2) Pour the nano-SiO2-doped WPU solution into a glass dish with a film-laying height of 5 mm. Bake the glass dish at 85°C for 30 min and then at 130°C for 2 h to obtain a dried film.

[0131] (3) immersing the dried film in a 23 g / L sodium hydroxide aqueous solution for alkali reduction hydrolysis treatment at a bath ratio of 1:10 to obtain a nano-SiO2-doped WPU film;

[0132] The alkali reduction hydrolysis process is as follows: heating to 100°C at a rate of 2°C / min, and hydrolyzing at 100°C for 60 minutes.

[0133] Depend on Figure 2-5 It can be seen that the surface of the nano-SiO2 doped WPU film prepared in Example 16 has many irregular particles, which may be the hydrolysis product of SiO2 sol in the alkaline hydrolysis process; the surface of the nano-SiO2 doped WPU film prepared in Example 17 has many gaps, which are the holes left after the SiO2 sol is hydrolyzed under alkaline conditions. When magnified 5k times and 10k times, some spherical substances can be seen on the surface, which are part of the SiO2 sol that has not been hydrolyzed; the surface of the nano-SiO2 doped WPU film prepared in Example 18 and Example 19 has many pores and some irregular particles. The irregular granular material may be the product of SiO2 alkaline hydrolysis; there are many pores on the surface because after the alkaline reduction hydrolysis, the SiO2 in the film is hydrolyzed, and pores are formed at the original position of SiO2.

[0134] Embodiment 20

[0135] This embodiment discloses a method for preparing microfiber synthetic leather based on waterborne polyurethane, comprising the following steps:

[0136] The ultrafine fiber leather base cloth is immersed in the WPU solution, double-dipping and double-rolling, the liquid carrying rate is 100%, and it is first dried at 85°C for 25 minutes and then dried at 130°C for 20 minutes to obtain the ultrafine fiber synthetic leather grey cloth;

[0137] The microfiber synthetic leather grey cloth was immersed in a 23 g / L sodium hydroxide aqueous solution for alkali reduction hydrolysis treatment, with a bath ratio of 1:10, to obtain a waterborne polyurethane-based microfiber synthetic leather;

[0138] The alkali reduction hydrolysis process is as follows: heating to 100°C at a rate of 2°C / min, and hydrolyzing at 100°C for 60 minutes.

[0139] Embodiment 21

[0140] This embodiment discloses a method for preparing microporous moisture-heat migration-resistant ultra-fiber synthetic leather based on waterborne polyurethane, comprising the following steps:

[0141] Step 1: Preparation of nano-SiO2 doped WPU solution

[0142] The nano-SiO2 sol prepared in Example 2 was mixed with WPU, with the mass ratio of nano-SiO2 sol to WPU being 1:3, and stirred for 30 minutes to obtain a nano-SiO2 doped WPU solution;

[0143] Step 2: Preparation of microporous moisture-heat migration-resistant microfiber synthetic leather based on waterborne polyurethane

[0144] The ultrafine fiber leather base cloth is immersed in the nano-SiO2 doped WPU solution, double-immersed and double-rolled, with the liquid rate of 100%, first dried at 85°C for 25 minutes, and then dried at 130°C for 20 minutes to obtain the ultrafine fiber synthetic leather grey cloth;

[0145] The microfiber synthetic leather grey cloth was immersed in a 23 g / L sodium hydroxide aqueous solution for alkali reduction hydrolysis treatment, with a bath ratio of 1:10, to obtain a microporous moisture-heat migration-resistant microfiber synthetic leather based on waterborne polyurethane;

[0146] The alkali reduction hydrolysis process is as follows: heating to 100°C at a rate of 2°C / min, and hydrolyzing at 100°C for 60 minutes.

[0147] Embodiment 22

[0148] This embodiment discloses a method for preparing microporous moisture-heat migration-resistant ultra-fiber synthetic leather based on waterborne polyurethane, comprising the following steps:

[0149] Step 1: Preparation of nano-SiO2 doped WPU solution

[0150] The nano-SiO2 sol prepared in Example 3 was mixed with WPU, with a mass ratio of nano-SiO2 sol to WPU of 1:3, and stirred for 30 minutes to obtain a nano-SiO2 doped WPU solution;

[0151] Step 2: Preparation of microporous moisture-heat migration-resistant microfiber synthetic leather based on waterborne polyurethane

[0152] The ultrafine fiber leather base cloth is immersed in the nano-SiO2 doped WPU solution, double-immersed and double-rolled, with the liquid rate of 100%, first dried at 85°C for 25 minutes, and then dried at 130°C for 20 minutes to obtain the ultrafine fiber synthetic leather grey cloth;

[0153] The microfiber synthetic leather grey cloth was immersed in a 23 g / L sodium hydroxide aqueous solution for alkali reduction hydrolysis treatment, with a bath ratio of 1:10, to obtain a microporous moisture-heat migration-resistant microfiber synthetic leather based on waterborne polyurethane;

[0154] The alkali reduction hydrolysis process is as follows: heating to 100°C at a rate of 2°C / min, and hydrolyzing at 100°C for 60 minutes.

[0155] Embodiment 23

[0156] This embodiment discloses a method for preparing microporous moisture-heat migration-resistant ultra-fiber synthetic leather based on waterborne polyurethane, comprising the following steps:

[0157] Step 1: Preparation of nano-SiO2 doped WPU solution

[0158] The nano-SiO2 dispersion prepared in Example 4 was mixed with WPU, with a mass ratio of the nano-SiO2 dispersion to WPU of 1:3, and stirred for 30 minutes to obtain a nano-SiO2-doped WPU solution;

[0159] Step 2: Preparation of microporous moisture-heat migration-resistant microfiber synthetic leather based on waterborne polyurethane

[0160] The ultrafine fiber leather base cloth is immersed in the nano-SiO2 doped WPU solution, double-immersed and double-rolled, with the liquid rate of 100%, first dried at 85°C for 25 minutes, and then dried at 130°C for 20 minutes to obtain the ultrafine fiber synthetic leather grey cloth;

[0161] The microfiber synthetic leather grey cloth was immersed in a 23 g / L sodium hydroxide aqueous solution for alkali reduction hydrolysis treatment, with a bath ratio of 1:10, to obtain a microporous moisture-heat migration-resistant microfiber synthetic leather based on waterborne polyurethane;

[0162] The alkali reduction hydrolysis process is as follows: heating to 100°C at a rate of 2°C / min, and hydrolyzing at 100°C for 60 minutes.

[0163] Embodiment 24

[0164] This embodiment discloses a method for preparing microporous moisture-heat migration-resistant ultra-fiber synthetic leather based on waterborne polyurethane, comprising the following steps:

[0165] Step 1: Preparation of nano-SiO2 doped WPU solution

[0166] The nano-SiO2 dispersion prepared in Example 5 was mixed with WPU, with a mass ratio of the nano-SiO2 dispersion to WPU of 1:3, and stirred for 30 minutes to obtain a nano-SiO2-doped WPU solution;

[0167] Step 2: Preparation of microporous moisture-heat migration-resistant microfiber synthetic leather based on waterborne polyurethane

[0168] The ultrafine fiber leather base cloth is immersed in the nano-SiO2 doped WPU solution, double-immersed and double-rolled, with the liquid rate of 100%, first dried at 85°C for 25 minutes, and then dried at 130°C for 20 minutes to obtain the ultrafine fiber synthetic leather grey cloth;

[0169] The microfiber synthetic leather grey cloth was immersed in a 23 g / L sodium hydroxide aqueous solution for alkali reduction hydrolysis treatment, with a bath ratio of 1:10, to obtain a microporous moisture-heat migration-resistant microfiber synthetic leather based on waterborne polyurethane;

[0170] The alkali reduction hydrolysis process is as follows: heating to 100°C at a rate of 2°C / min, and hydrolyzing at 100°C for 60 minutes.

[0171] Depend on Figure 6-10 It can be seen that the polyurethane in the microfiber synthetic leather based on waterborne polyurethane prepared in Example 20 is gathered on both sides of the synthetic leather after alkali reduction treatment, with less polyurethane and more pores in the middle position. These are the holes left by the waterborne polyurethane after the evaporation of water in the synthetic leather during the drying process, indicating that the waterborne microfiber leather has poor resistance to moisture and heat migration; the microporous moisture and heat migration resistant microfiber synthetic leather based on waterborne polyurethane prepared in Examples 21-24 has a more uniform distribution of polyurethane in the microfiber leather prepared from WPU solution doped with nano-SiO2, indicating that SiO2 doping can improve the moisture and heat migration resistance of the waterborne microfiber leather.

[0172] Test example

[0173] (1) The specific surface area and porosity of the microfiber leather prepared in Examples 20-24 were measured using a specific surface area and porosity analyzer (SAP). The measurement results are shown in Table 4:

[0174] Table 4 Specific surface area, pore volume and pore size of each microfiber synthetic leather after alkaline hydrolysis

[0175]

[0176] It can be seen from Table 4 that the specific surface area and pore volume of pure water-based microfiber leather are smaller than those of microfiber leather prepared by nano-SiO2 doped WPU solution, while the pore size is the opposite. The specific surface area and pore volume of the synthetic leather become larger after SiO2 doping because after alkali reduction hydrolysis, the SiO2 in the nano-SiO2 doped WPU solution applied on the microfiber base cloth is hydrolyzed, and the volume occupied by SiO2 is vacant to form many pores. The more and smaller the pores, the larger the specific surface area of ​​the synthetic leather; after SiO2 doping, the pore size of the synthetic leather becomes smaller, the pure water-based microfiber leather without SiO2 doping has few and large pores, while the microfine leather doped with SiO2 has dense and small pores.

[0177] The particle size of the nano-SiO2 sol prepared in Example 2 is larger than that of the nano-SiO2 sol prepared in Example 3, but the specific surface area and pore volume of the synthetic leather prepared after doping with WPU are smaller, and the pore size is larger; the particle size of the nano-SiO2 dispersion prepared in Example 4 is larger than that of the nano-SiO2 dispersion prepared in Example 5, but the specific surface area and pore volume of the synthetic leather prepared after doping with WPU are smaller, and the pore size is larger; it can be seen that the synthetic leather prepared after doping with SiO2 solution with larger particle size with WPU has smaller specific surface area and pore volume, and larger pore diameter.

[0178] (2) The feel of the microfiber leathers prepared in Examples 20-24 was measured using a fabric evaluation instrument. The results are shown in Table 5:

[0179] Table 5 Softness index of each microfiber synthetic leather after alkaline hydrolysis

[0180]

[0181] It can be seen from Table 5 that the softness of the nano-SiO2 sol and WPU doped microfiber leather prepared in Example 2 is better than that of the pure water-based microfiber leather. The softness of the nano-SiO2 sol and WPU doped microfiber leather prepared in Example 3 is similar to that of the pure water-based microfiber leather; however, the softness of the synthetic leather doped with nano-SiO2 dispersion is worse than that of the synthetic leather made with deionized water; within a certain range, the smaller the pore size, the lower the softness, but the smaller the pore size, the better, and it should be controlled within an appropriate range.

[0182] (3) The microfiber synthetic leather based on waterborne polyurethane prepared in Examples 20-24 was subjected to dyeing test. Fig.11As shown in the figure, from top to bottom are the dyed cross-sections of the microfiber synthetic leather based on waterborne polyurethane obtained in Example 20, Example 21, Example 22, Example 23 and Example 24. After roller dyeing, the cross-section of the pure WPU synthetic leather is light in the middle and dark in both sides, with a white core phenomenon, indicating that the water-based microfiber leather has poor heat migration resistance. During drying, the dye moves to both sides of the fiber along with the movement of WPU, resulting in uneven dyeing; while the cross-section of the water-based microfiber leather modified with nano-SiO2 is more uniform after dyeing, without obvious white core phenomenon, indicating that the addition of nano-SiO2 fixes the position of WPU, making it difficult for WPU to migrate during drying, and the dye is not easy to move to the fiber surface.

[0183] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing microporous moisture-heat migration-resistant ultra-fiber synthetic leather based on waterborne polyurethane, characterized in that: The following steps are involved: Step 1: Preparation of nano-SiO2 doped WPU solution The nano-SiO2 system and the WPU solution are mixed in a mass ratio of 1:(1-3), and after stirring, a nano-SiO2-doped WPU solution is obtained; Step 2: Preparation of microporous moisture-heat migration-resistant microfiber synthetic leather based on waterborne polyurethane The ultrafine fiber leather base cloth is immersed in the nano-SiO2 doped WPU solution, double-immersed and double-rolled, and dried to obtain the ultrafine fiber synthetic leather grey cloth; The microfiber synthetic leather grey cloth is immersed in an alkali solution for alkali reduction and hydrolysis treatment to obtain a microporous moisture-heat migration-resistant microfiber synthetic leather based on waterborne polyurethane.

2. The method for preparing microporous moisture-heat migration-resistant ultra-fiber synthetic leather based on waterborne polyurethane according to claim 1, characterized in that: In the step 1, the nano-SiO2 system includes any one of nano-SiO2 sol and nano-SiO2 dispersion.

3. The method for preparing microporous moisture-heat migration-resistant ultra-fiber synthetic leather based on waterborne polyurethane according to claim 2, characterized in that: The nano-SiO2 sol is prepared by the following steps: Sodium dodecylbenzenesulfonate and concentrated hydrochloric acid are added to deionized water and mixed. After the sodium dodecylbenzenesulfonate is completely dissolved, methyltrimethoxysilane is added dropwise. After the addition is completed, the reaction is stirred. After the reaction is completed, the temperature is increased to continue the reaction. After the reaction is completed, the reaction is cooled and the pH value is adjusted to 6-7 to obtain a nano-SiO2 sol.

4. The method for preparing microporous moisture-heat migration-resistant ultra-fiber synthetic leather based on waterborne polyurethane according to claim 3, characterized in that: The stirring reaction conditions are to maintain a stirring speed of 300 r / min, first react at a temperature of 20-40° C. for 0.5-1.5 h, then raise the temperature to 50-70° C., and continue to react for 0.5-2.5 h.

5. The method for preparing microporous moisture-heat migration-resistant ultra-fiber synthetic leather based on waterborne polyurethane according to claim 3, characterized in that: When preparing nano-SiO2 sol, the dosage of methyltrimethoxysilane is 20-150g / L, the dosage of sodium dodecylbenzenesulfonate is 0.2-1.2g / L, and the dosage of concentrated hydrochloric acid is 0.5-5g / L; The concentrated hydrochloric acid is a 37 wt % hydrochloric acid aqueous solution.

6. The method for preparing microporous moisture-heat migration-resistant ultra-fiber synthetic leather based on waterborne polyurethane according to claim 2, characterized in that: The nano-SiO2 dispersion is prepared by uniformly dispersing nano-SiO2 particles in deionized water.

7. The method for preparing microporous moisture-heat migration resistant ultra-fiber synthetic leather based on waterborne polyurethane according to claim 6, characterized in that: The nano-SiO2 particles used in the preparation of the nano-SiO2 dispersion have a particle size of 30nm-3μm and a content of 20-240g / L. The dispersion methods include stirring dispersion, ultrasonic dispersion, and high-performance disperser dispersion.

8. The method for preparing microporous moisture-heat migration-resistant ultra-fiber synthetic leather based on waterborne polyurethane according to claim 1, characterized in that: In the step 2, the liquid rate after the double dipping and double rolling is 100%, and the drying conditions are first drying at 80-100° C. for 15-30 min, and then drying at 120-150° C. for 10-30 min.

9. The method for preparing microporous moisture-heat migration resistant ultra-fiber synthetic leather based on waterborne polyurethane according to claim 1, characterized in that: In the step 2, the alkali reduction hydrolysis treatment comprises immersing the microfiber synthetic leather grey cloth in an alkali solution for hydrolysis treatment, the bath ratio of the grey cloth to the alkali solution is 1:10, and the alkali solution comprises a 4-30 g / L sodium hydroxide aqueous solution; The alkali reduction hydrolysis process comprises: heating to 95-125° C. at a speed of 2° C. / min, and maintaining the temperature for hydrolysis for 30-90 minutes.

10. Application of the microporous moisture-heat migration resistant microfiber synthetic leather based on waterborne polyurethane prepared by the method for preparing microporous moisture-heat migration resistant microfiber synthetic leather based on waterborne polyurethane as described in claims 1-9 in automobile interior decoration.

Citation Information

Cited By

  • Bionic breathable composite material based on microporous nanofiber membrane

    CN120666567A